Relación entre el riesgo crediticio y la inclusión financiera del Banco de la Nación en la región de Loreto 2018–2024 - Hidalgo Pfennig, Ana Estela (2025)
This study investigates the relationship between credit risk and financial inclusion at Banco de la Nación in the Loreto region from 2018 to 2024. Employing a quantitative time-series approach with quarterly data, we constructed a composite risk index—combining non-performing loan rates, provision coverage ratios, and credit liquidity—and a composite inclusion index—incorporating deposit volumes, outstanding loans, branch network size, and ATM density per capita. Spearman’s rank correlations were used to test the principal hypothesis of a positive linkage between risk and inclusion, as well as three specific hypotheses examining the pairs: non-performing loans versus deposits, provision coverage versus deposits, and liquidity versus lending. Findings reveal a strong, statistically significant correlation for the main hypothesis (ρ = 0.68, p < 0.001) and moderately robust correlations for the specific tests (ρ ranging from 0.54 to 0.61, p < 0.01). These results confirm that as banking access expanded in Loreto, credit exposure rose in tandem, highlighting the tension between the bank’s social mandate and the imperative to safeguard portfolio health. The study underscores the need for early warning systems, tailored financial education programs, and transparent provisioning policies to foster sustainable inclusion without compromising institutional solvency.